Enhancement of specific absorption rate in CoO.7ZnO.3Fe2O4 and CoO.5ZnO.5Fe2O4 composite nanoparticles - Nam, P. H.; Bach, T. N.; Nam, N. H.; Quynh, N. V.; Truong, N. X.; Manh, D. H.; Nguyen, L. H.; Phong, P. T. (Vietnam Journal of Science and Technology, 2021)
We report the advantage of the exchange coupling between a magnetically soft (MnFe2O4) and magnetically hard (Co0.7Zn0.3Fe2O4 and Co0.5Zn0.5Fe2O4) magnetic phase to increase the specific absorption rate (SAR) in magnetic inductive heating. All samples were synthesized by hydrothermal method. While the saturation magnetization (Ms) of two composite nanoparticles is approximately 1.1 times higher the Ms of single-component, the SAR is more 2 times than those values of single-component.